In vitro bioaccessibility of antioxidant compounds from structured fruits developed with gellan gum and agar - Rodrigues Leal, Amanda (Revista Ciência Agronômica, 2023)
This study aims to evaluate the bioaccessibility of antioxidant compounds of structured fruits. Samples were prepared with 50% of each pulp (mango/caja, mango/cashew apple and mango/acerola), agar and gellan gum (low acyl-LA and high acyl-HA) in LA:HA ratios of: 100:0, 75:25 and 50:50, in a concentration of 0.75%. There was a reduction in the antioxidant compounds contents after in vitro digestion. The bioaccessible ascorbic acid levels ranged from 15.10% (LA100/HA0 mango/acerola) to 71.18% (LA50/HA50 mango/cashew apple); Total Extractable Polyphenols (TEP) ranged from 24.58% (mango/caja pulp) to 75.50% (LA75/HA25 mango/acerola); antioxidant activity ranged from 21.10% (LA75/HA25 mango/caja) to 51.05% (LA75/HA25 mango/acerola). Mango/acerola ascorbic acid bioaccessibility was lower and the mango/cashew apple HA gellan gum sample antioxidant activity was higher than pulp, probably due to temperature increasing at processing. It was concluded that the agar and gellan gum (HA and LA) hydrocolloids were able to contain these compounds in the production process of the structured and during digestion, which proves the similarity of structured fruits with fresh pulps.